Plasma proteome profiling reveals differentially expressed lipopolysaccharide-binding protein among leptospirosis patients - Low, Cheng Yee; Thian, Leslie Lung Than; Ling, King Hwa; Lin, Qingsong; Sekawi, Zamberi (Elsevier, 2020)
Background: Human leptospirosis, or commonly known as “rat urine disease” is a zoonotic disease that is caused by the bacteria called Leptospira sp. The incidence rate of leptospirosis has been under-reported due to its unspecific clinical symptoms and the limitations of current laboratory diagnostic methods. Leptospirosis can be effectively treated with antibiotics in the early stage, and it is a curable disease but the accuracy to diagnose the infection is rarely achieved. Methods: The present pilot study investigated plasma protein profiles of leptospirosis patients and compared them against two control groups which consisted of dengue patients and healthy individuals. The plasma protein digests were analyzed using shotgun approach by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Protein abundances were estimated from the exponentially modified protein abundance index (emPAI) values. Plasma proteins in leptospirosis patients with at least two-fold differential expression compared to dengue and healthy control groups (p < 0.05, ANOVA) were identified. Results: Lipopolysaccharide (LPS)-binding protein (LBP) was found to be the only protein that has significant different expression between leptospirosis and the two control groups. The expression levels of leucine-rich alpha-2-glycoprotein (LRG1) and alpha-1-antichymotrypsin (ACT) were different significantly between leptospirosis and healthy group but not to the dengue control group. Conclusion: This is the first plasma proteome-based study on leptospirosis that reports the differential expression of LBP compared to both dengue and healthy controls, which has not been previously reported in the context of leptospirosis.